2014
DOI: 10.3906/zoo-1405-72
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of Annelida from the coasts of Turkey

Abstract: IntroductionThe phylum Annelida is composed of segmented worms and includes 2 classes, namely Polychaeta (marine worms) and Clitellata (oligochaetes and leeches) (WoRMS, 2014). The current estimation of the number of annelida species revealed that 13,721 species are present in the world's oceans (Appeltans et al., 2012). The majority of species belong to polychaetes (12,632 species), followed by oligochaetes (910 species) and leeches (179 species). In the Mediterranean Sea, 1181 Annelida species have been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 65 publications
3
96
0
1
Order By: Relevance
“…The existence in Syllidae of complexes of sibling species that are morphologically identical and occupy disjunct or extremely wide distribution areas has been demonstrated a number of times by more detailed morphological studies [123] or molecular methods [124]. However, Erinaceusyllis serratosetosa and S. pectinans, which are known from a few localities of the Iberian Peninsula, seem to be true NIS [24,62], although no human-mediated pathway has been identified for these species. The family Syllidae is not unique in this respect.…”
Section: Some Cryptogenic Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence in Syllidae of complexes of sibling species that are morphologically identical and occupy disjunct or extremely wide distribution areas has been demonstrated a number of times by more detailed morphological studies [123] or molecular methods [124]. However, Erinaceusyllis serratosetosa and S. pectinans, which are known from a few localities of the Iberian Peninsula, seem to be true NIS [24,62], although no human-mediated pathway has been identified for these species. The family Syllidae is not unique in this respect.…”
Section: Some Cryptogenic Speciesmentioning
confidence: 99%
“…With just two NIS, the inventory is much less in Malta [59], but it is a much smaller country, whereas the list from Turkey of 66 species is by far the largest, [24]. In fact, compilations for the Mediterranean Sea are more complete as 132 NIS polychaete species [60,61] have been recorded, of which at least 26 are known to be established in the western area of this sea [62] The great difference between the Mediterranean and Atlantic national inventories might suggest that the former is under a stronger invasion pressure.…”
Section: Is the Situation In Spain And Portugal Worse Than In Other Ementioning
confidence: 99%
See 1 more Smart Citation
“…The marine coastal biota of the Levant Sea is susceptible to Lessepsian invasion through the Suez Canal (Çinar et al, 2005b; Çinar et al, 2006). Previous studies from the Levant Sea have reported a total of 77 alien polychaete species (Çinar et al 2014;Zenetos et al, 2010), 61% of which are known to be Lessepsian immigrants, and up to 86% of which could have originated in the Red Sea and Indo-Pacific. With the ongoing expansion of the "New Suez Canal" (Galil et al, 2015), this number is expected to become even higher.…”
Section: Iphione Muricata Savigny In Lamarck 1818mentioning
confidence: 99%
“…Up to now, no any records belong these species have been reported in Turkey (Arslan, 2006;Çınar et al, 2011;Çınar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%